Extraction of Ontological Information based on Semantic Analysis (International Journal of Engineering and Computer Science, 2013)
In the rapid growth of communication field and updating of data rate that make the task to find relevant information retrieval is more difficult in the modern world. Probably User always wants to access information from the web search log, to gain the context-based data for their required information. Many researchers worked on the process of content-based information retrieval process in the web search engine. The model addressed inability to describe relations between search terms. In this paper, present an ontological based pattern description technique is the extraction of semantic data from search log through the query processing system. An experiment shows that this model can increase a usage scenario of the person.